(untitled) - Adriaanse, John (New York, NY., 2005)
Contract law is a key part of the construction industry, and takes up a significant part of any degree course in building or construction. A wide range of practitioner's tomes currently exist but there is a distinct lack of student texts that explain the essentials in a concise and accessible manner. The purpose of this book is to bridge this gap between undergraduates and practitioners and provide a helpful guide to the essentials of construction contract law including: how the law has developed, the reasoning behind the key contract clauses, and how contract law is applied in practice.
Keywords: Private law,Construction,Construction contract law; Law and legislation; Great britain,Great britain